2019
DOI: 10.1111/jne.12673
|View full text |Cite
|
Sign up to set email alerts
|

NDP‐MSH reduces oxidative damage induced by palmitic acid in primary astrocytes

Abstract: Recent findings relate obesity to inflammation in key hypothalamic areas for body weight control. Hypothalamic inflammation has also been related to oxidative stress.Palmitic acid (PA) is the most abundant free fatty acid found in food, and in vitro studies indicate that it triggers a pro-inflammatory response in the brain.Melanocortins are neuropeptides with proven anti-inflammatory and neuroprotective action mediated by melanocortin receptor 4 (MC4R), but little is known about the effect of melanocortins on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
(91 reference statements)
0
6
0
1
Order By: Relevance
“…There are some limitations in our study. NDP-MSH had been reported to possess multiple beneficial properties in a central nervous system disease, including anti-inflammation, anti-apoptosis, and anti-oxidation [13, 31, 34, 38, 39]. In this study, we only investigated the neuroprotective functions of NDP-MSH on neuroinflammation and BBB integrity after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations in our study. NDP-MSH had been reported to possess multiple beneficial properties in a central nervous system disease, including anti-inflammation, anti-apoptosis, and anti-oxidation [13, 31, 34, 38, 39]. In this study, we only investigated the neuroprotective functions of NDP-MSH on neuroinflammation and BBB integrity after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have associated SAFAs as a primary cause of cell death [ 108 ]. In this regard, it has been reported that PA could affect the cell viability of different brain cells, such as the neuroblastoma SH-SY5Y [ 109 ], glioblastoma T98G [ 110 , 111 ], microglial cells BV-2 [ 112 ], primary microglia [ 40 ], primary neurons [ 31 ], and primary astrocytes [ 113 , 114 , 115 , 116 ]. Although it is known that the PA could affect different brain cells through different cellular mechanisms, these are not clear.…”
Section: Pathways Involved In Palmitic Acid-induced Toxicitymentioning
confidence: 99%
“…Astrocytes were obtained from cerebral cortices of male/female 1-2-day-old Wistar rat pups, as previously described [15]. Wild-type and SR-A knockout mice-derived cortical astrocyte cultures were prepared using the protocol of von Bernhardi and Eugenín [16].…”
Section: Astrocyte Primary Culturesmentioning
confidence: 99%